Krishantering, hushåll och stormen Gudrun : Att analysera hushålls krishanteringsförmåga och sårbarheter - Guldåker, Nicklas (Meddelanden från Lunds universitets geografiska institution. Avhandlingar, 2009)
Severe crises and disasters such as the Hurricane Gudrun and their consequences will probably occur in the future. However, there are many uncertainties concerning disasters and their effects. New scientific approaches and methods for crisis and disaster research must be developed to increase the knowledge and ability of societies to manage known and unknown threats. Substantial research on the emergency preparedness and crises and disaster management capability of agencies, organizations and institutions exists in Sweden and the Nordic countries. Despite this, there is a general lack of research on the crisis management capability of citizens, individuals, groups and households. This thesis should be seen as a complementary approach within the crisis and disaster research field. The aim of the thesis is to develop and test a theoretical framework for analyzing the crisis management capability and vulnerability of households, and external actors' interaction with and assistance to vulnerable households during severe emergencies and disasters. The design of the theoretical framework including an analytical model for description and analysis of household crisis management capability and vulnerability departs from a hurricane-perspective, with a particular focus on the hurricane Gudrun. The theoretical framework draws on the concept of the household, concepts from actor-network theory (ANT) and time-geography. Concepts such as actor, actant, actor-network, relations, network stability, mobilization, immutable mobiles, projects, restrictions, pockets of local order etc, together provide an important basis for the analysis of household crisis management capability and vulnerability. Based on an analysis of interviews with 41 affected members of households and focus group interviews with 30 municipal officials, a discussion of what constitutes internal and external crisis management capability from a household perspective, is presented. The thesis results in a theoretical framework and a model useful for analysis of household management capability and vulnerability during other severe emergencies than those caused by hurricanes. In this way, the thesis provides a contribution to the development of a more general analytical model related to household crisis management capability and vulnerability. The thesis also generates significant and useful results and strategies involving both household crisis management capability and the capability of external societal actors’ capability to interact with and support vulnerable households during severe crises and disasters.
Keywords: Household; Actor-network theory; Hurricane Gudrun; Crisis management; Vulnerability; Crisis management capability; Time-geography; Krishantering; Stormen Gudrun; Krishanteringsförmåga; Hushåll; Aktör-nätverksteorin; Sårbarhet; Tidsgeografi